Human resource development for future basic occupational health services in Malaysia - Samsuddin, Niza; A. Rahman, Nor Azlina; Razali, Ailin; Yusof, Muhammad Zubir; Abdullah Hair, Ahmad Fitri; Manivasagam, Dayanath; Hullon, Rajinderjit Singh; Nik Mohamed, Nik Mohamed Nizan (Kulliyyah of Allied Health Sciences, IIUM, 2019)
A guideline on Basic Occupational Health Services (BOHS) has been established jointly by ILO/WHO/ICOH in response to poor achievements of the Occupational Health Services (OHS), especially among workers in small and medium enterprises at the global level. Malaysia. The international guideline describes competent and skilled human resources as an essential strategy for BOHS implementation. This commentary will discuss the challenges faced by current occupational health personnel providing OHS in Malaysia and proposes improvements of human resource development for future BOHS in Malaysia to ensure fair and better OHS coverage for Malaysian workers.